Opening the cocaine economy by providing within-session access to a cheaper source of cocaine makes demand for it more elastic. Issue 5 (August 2020) - Kearns, David N.; Silberberg, Alan
Abstract : Previous studies found that opening the cocaine economy by providing postsession access to cocaine had no effect on animals' demand for cocaine, whereas postsession access to saccharin or food made demand for these nondrug reinforcers more elastic. It is possible that there was no effect of economy type on cocaine taking in these earlier studies because of the delay to the postsession cocaine in the open economy. The present experiment tested whether forming an open economy by providing additional within-session cocaine, rather than postsession cocaine, would make rats' demand for cocaine more elastic. Saccharin was used as a nondrug comparison reinforcer. Three groups of rats pressed one lever for cocaine and one for saccharin on an ascending series of fixed ratio (FR) schedules where the number of responses required per reinforcer increased from 1 to 48 over sessions. In the open cocaine and open saccharin economy groups, rats had occasional access during the session to a third lever where cocaine or saccharin reinforcers, respectively, were always available on an FR-1 schedule. The main finding was that demand for cocaine was more elastic in the open cocaine economy group than in either of the other groups. Demand for saccharin was more elastic in the open saccharin economy group than in the open cocaine economy group. This study shows that cocaine taking is sensitive to economy type when the additional source of cocaine in an open economy is available close in time to when rats work for cocaine.